Social work practice : assessment, planning, intervention and review - Parker, Jonathan, ....- (Thousand Oaks, California : Sage, 2017)
This bestselling book will take you step-by-step through the four main aspects of social work practice - Assessment, Planning, Intervention and Review - giving you a complete foundation in each. It will introduce you to each process in a clear and accessible way, supporting you to both reflect on and apply what you have learnt in practice across settings and service user groups. The book will provide you with a theoretical foundation from which you can explore other aspects of social work. New to the fifth edition: an ethnographic approach' to social work focus on relationship and resilience revised exploration of the political context of social work updated emphasis on social justice and human rights.
Transforming social work practice - Mapped to the PCF